PENANGGULANGAN TINDAK KEJAHATAN PADA PENGGUNAAN MATA UANG VIRTUAL/ASET KRIPTO - Ricky Vandre Teguh Jaya; Patricia Rinwigati (LPPM Universitas Ekasakti Padang, 2023)
Cryptocurrency can be defined as a virtual currency that uses a peer-to-peer system so that it is decentralized, which can have positive and negative impacts, One of the negative impacts that are present is that crimes can occur by taking advantage of these present characteristics, so that an appropriate countermeasure is needed. The research method used is normative research with legal comparisons and deductive analysis, that differences in regulations from countries make it difficult for law enforcement in the event of cross-country crimes using cryptocurrency, given the different regulations between countries and limitations on jurisdiction, so a the basic framework of regulation and exchange of information implemented by the international community together and also implemented in positive legal rules by each country, in order to be able to tackle cryptocurrency-related crimes.